Spectrophotometric Quantification of Toxicologically Relevant Concentrations of Chromium(VI) in Cosmetic Pigments and Eyeshadow Using Synthetic Lachrymal Fluid Extraction. (4th January 2012) - Wurster Wurster, Sarah Sarah; Kratz Kratz, Evamaria Evamaria; Lachenmeier Lachenmeier, Dirk W. Dirk W.; Mildau Mildau, Gerd Gerd
Abstract : Chromium(VI) salts are possible contaminants of the chromium(III) pigments used as colorants in eyeshadow preparations. The use of products containing these contaminants poses acute risks for sensitization and contact allergies. Chromium(VI) compounds are also classified as carcinogenic to humans (IARC group 1). An analytical method to analyse trace levels of chromium(VI) in eyeshadow was developed in this study. The method is based on an extraction of the chromium(VI) from the sample using a maximum extraction with alkali and additionally with synthetic lachrymal fluid to simulate physiological conditions. Following derivatization with 1, 5-diphenylcarbazide, the extracted chromium(VI) is then quantified by spectrophotometry (540 nm). Validation tests indicated a method standard deviation (inter- and intraday) of 8.7% and a linear range up to 25 mg/kg. The average recovery was 107.9%, and the detection limit was 2.7 mg/kg. The applicability of the procedure was confirmed by the analysis of pigments and authentic eyeshadow matrices.